The Influence Of Creativity And Innovative Behavior On Employee Performance (Study Of Employees Working At Hotel Karebosi Premier Makassar) - Muhammad Fahrul Kahar; Mahlia Muis; Andi Reni (Lafadz Jaya Publisher, 2023)
This study aims to examine and analyze the effect of creativity on employee performance, the effect of innovative behavior on employee performance and the simultaneous influence of creativity and innovative behavior on employee performance. Data collection uses primary data obtained from employees who work at the Karebosi Premier Makassar hotel where sampling uses a saturated sample where all members of the population are sampled so that a sample of 51 respondents is determined. The results of the questionnaire have been tested for validity and reliability, as well as tested for classic assumptions in the form of Normality Assumptions, Multicollinearity Assumptions, and Heteroscedasticity. The data analysis method used multiple linear regression analysis with the help of the SPSS 23 (Statistical Program For Social Science) program. The results showed that both partially and simultaneously creativity and innovative behavior had a positive and significant effect on employee performance so that all hypotheses proposed were accepted.